Detection of Aspergillus fumigatus and a Mutation That Confers Reduced Susceptibility to Itraconazole and Posaconazole by Real-Time PCR and Pyrosequencing - Trama, Jason P. (American Society for Microbiology, 2005)
A real-time PCR and pyrosequencing method was developed to detect Aspergillus fumigatus in whole blood by amplifying the cyp51A gene and sequencing the codon for glycine 54. Mutations in this codon can result in amino acid substitutions that confer reduced susceptibility to itraconazole and posaconazole.